Epidemiologia y factores de riesgo asociados a nefropatia iga en latinoamerica - Romero Cordova, Marllely Carmita (Machala : Universidad Técnica de Machala, 2019)
Introduction: IgA Nephropathy, is one of the most prevalent glomerular diseases worldwide, is related to several risk factors such as: age, gender, ethnicity, hypertension, proteinuria, obesity, respiratory diseases use of non-steroidal anti-inflammatory drugs, among others. Objective: to determine the incidence and epidemiological prevalence, as well as the risk factors associated with the appearance of IgA nephropathy in Latin America. Materials and Methods: This is a retrospective study, with the acquisition of scientific evidence in the database PUBMED, MEDLINE, and EMBASE, with Latin American articles (Argentina, Brazil, Colombia, Peru, Uruguay and Venezuela), published between 2012 and 2018, He made a synthesis of the data and a critical summary of the results. Results: The results showed that focal and segmental glomerulosclerosis with 18.8% had a higher incidence, while IgA nephropathy with 12.8% was in second place among all types of glomerulonephritis. The risk factors according to the publications selected in this study were: male gender (58%), average age 31 years, hematuria (47%), arterial hypertension 17% and non-nephrotic proteinuria (47%) and nephrotic (22%). Conclusion: IgA deposit nephropathy is the second type of glomerulonephritis most common in Latin America and is among the top five worldwide. The appearance of the disease is especially related to the male gender, in the third decade of life, the presence of hematuria, and non-nephrotic proteinuria.
Introducción: La Nefropatía IgA, es una de las enfermedades glomerulares más prevalentes a nivel mundial, se encuentra relacionada con varios factores de riesgo como: edad, genero, etnia, hipertensión arterial, proteinuria, obesidad, enfermedades respiratorias uso de antinflamatorios no esteroideos, entre otros. Objetivo: determinar la incidencia y prevalencia epidemiológica, así como los factores de riesgo asociados a la aparición de nefropatía IgA en América Latina. Materiales y Métodos: Es un estudio retrospectivo, con adquisición de evidencia científica en la base de datos PUBMED, MEDLINE, y EMBASE, con artículos latinoamericanos (Argentina, Brasil, Colombia, Perú, Uruguay y Venezuela), publicados entre 2012 y 2018, se realizó una síntesis de los datos y un resumen crítico de los resultados. Resultados: Los resultados mostraron que glomeruloesclerosis focal y segmentaria con 18,8% tiene mayor incidencia, mientras que la nefropatía por IgA con 12,8% se ubica en el segundo lugar entre todos los tipos de Glomerulonefritis. Los factores de riesgo según las publicaciones seleccionadas en este estudio fueron: género masculino (58%), edad promedio 31 años, hematuria (47%), hipertensión arterial 17% y proteinuria no nefrótico (47%) y nefrótico (22%). Conclusión: la nefropatía por depósitos de IgA es el segundo tipo de Glomerulonefritis más común en América latina y se encuentra entre los cinco primeros a nivel mundial. La aparición de la enfermedad está relacionada especialmente al género masculino, en la tercera década de la vida, presencia de hematuria y proteinuria no nefrótica.
Keywords: GLOMERULONEFRITIS IGA; EPIDEMIOLOGIA; FACTORES DE RIESGO